2017
DOI: 10.3389/fmicb.2017.01438
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Bacillus amyloliquefaciens Strains Reveals a Core Genome with Traits for Habitat Adaptation and a Secondary Metabolites Rich Accessory Genome

Abstract: The Gram positive, non-pathogenic endospore-forming soil inhabiting prokaryote Bacillus amyloliquefaciens is a plant growth-promoting rhizobacterium. Bacillus amyloliquefaciens processes wide biocontrol abilities and numerous strains have been reported to suppress diverse bacterial, fungal and fungal-like pathogens. Knowledge about strain level biocontrol abilities is warranted to translate this knowledge into developing more efficient biocontrol agents and bio-fertilizers. Ever-expanding genome studies of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 122 publications
14
104
0
1
Order By: Relevance
“…Strain ZJU1 is a cultured representative that was initially identified by 16S rRNA analysis as Bacillus amyloliquefaciens. It is well-established that the species B. amyloliquefaciens is associated with many plants (Belbahri et al, 2017), whereas to the best of our knowledge, this is the first report of the presence of B. amyloliquefaciens inside woody tree leaves. Phylogenetic reconstruction based on 16S rRNA sequences also showed that ZJU1 forms a phylogenetic lineage distinct from other B. amyloliquefaciens strains (Figure 2A).…”
Section: Isolation and Identification Of The Endophytic Bacterium Bmentioning
confidence: 74%
“…Strain ZJU1 is a cultured representative that was initially identified by 16S rRNA analysis as Bacillus amyloliquefaciens. It is well-established that the species B. amyloliquefaciens is associated with many plants (Belbahri et al, 2017), whereas to the best of our knowledge, this is the first report of the presence of B. amyloliquefaciens inside woody tree leaves. Phylogenetic reconstruction based on 16S rRNA sequences also showed that ZJU1 forms a phylogenetic lineage distinct from other B. amyloliquefaciens strains (Figure 2A).…”
Section: Isolation and Identification Of The Endophytic Bacterium Bmentioning
confidence: 74%
“…Mugsy was used to align the genomic data, and the bx-python tool kit (https://bitbucket.org/james_taylor/bx-python) was used to concatenate homologous blocks. RAxML version 7.2.8 (24) and FigTree version 1.3.1 (http://tree.bio.ed.ac.uk /software/fifigtree/) was used to construct and visualise phylogenetic trees from concatenated blocks using 1000 bootstrap replicates and the maximum-likelihood method. The CAZyome phylogenomic analysis was performed on homologous CAZy genes.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Improving upon its previous iterations, BAGEL3 introduces the ability to input raw DNA sequences instead of annotated genomes, and broadens the detection of gene clusters to include RiPPs (examples described include cyanobactins, sactipeptides, and linaridins). A range of antimicrobial peptide‐encoding gene clusters has been identified using BAGEL3, from Staphylococcus capitis TE8, Bacillus pumilus , and Bacillus amyloliquefaciens . For example, while genome‐mining work of Belbahri et al on plant‐associated bacteria Bacillus amyloliquefaciens describes known BGCs for fengycin, bacilysin, and mersacidin (among others), it also discusses hundreds of unknown secondary metabolites of multiple subclasses (e.g., microcins, bacteriocins, and NRPSs) requiring further characterization from numerous genome‐sequenced B. amyloliquefaciens strains.…”
Section: Clustersmentioning
confidence: 99%
“…For example, while genome‐mining work of Belbahri et al on plant‐associated bacteria Bacillus amyloliquefaciens describes known BGCs for fengycin, bacilysin, and mersacidin (among others), it also discusses hundreds of unknown secondary metabolites of multiple subclasses (e.g., microcins, bacteriocins, and NRPSs) requiring further characterization from numerous genome‐sequenced B. amyloliquefaciens strains. This is a potential “gold‐mine” of peptide antibiotics . Another tool for the genome annotation of prokaryotes is PRISM3 (Prediction Informatics for Secondary Metabolomes: https://magarveylab.ca/prism/), which, alongside genome mining, focuses upon chemical structure prediction of nonribosomal peptides and type I and II polyketides .…”
Section: Clustersmentioning
confidence: 99%